2019
DOI: 10.3390/ani9070425
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Anatomical Sites for the Measurement of Infrared Body Surface Temperature Variation in Response to Handling and Transport

Abstract: This study aimed at validating the anatomical sites for the measurement of infrared (IR) body surface temperature as a tool to monitor the pigs’ response to handling and transport stress. The selected anatomical sites were the neck (infrared neck temperature—IRNT), rump (infrared rump temperature—IRRT), orbital (infrared orbital temperature—IROT) and behind ears (infrared behind ears temperature—IRBET) regions. A total of 120 pigs were handled from the finishing pen to the loading dock through a handling test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 68 publications
4
25
0
Order By: Relevance
“…Lewis [9] reported a wider variability with the average EST of piglets during road transport, ranging from 36.2 °C in summer to 23.1 °C in winter. Although we have not found studies that measure the EST in adult pigs continuously during road transport, Rocha et al [28] report average skin temperatures of 30.89 °C-36.02 °C, measured using thermography, which is similar to our results. The relationship between the surface temperature determined by thermography and the skin temperature determined by probes in contact with the animal has been reported before [29], in which the emissivity is calculated based on the assumption that both temperature measurements are similar.…”
Section: Pig Skin Temperaturesupporting
confidence: 90%
“…Lewis [9] reported a wider variability with the average EST of piglets during road transport, ranging from 36.2 °C in summer to 23.1 °C in winter. Although we have not found studies that measure the EST in adult pigs continuously during road transport, Rocha et al [28] report average skin temperatures of 30.89 °C-36.02 °C, measured using thermography, which is similar to our results. The relationship between the surface temperature determined by thermography and the skin temperature determined by probes in contact with the animal has been reported before [29], in which the emissivity is calculated based on the assumption that both temperature measurements are similar.…”
Section: Pig Skin Temperaturesupporting
confidence: 90%
“…In that same study, Rocha et al [106], found an increased heart rate during loading in the pigs that received rough handling, and that the pigs subjected to the long walk showed higher saliva cortisol concentrations caused by the physical and emotional stress due to the long distance and high speed of the walk.…”
Section: Infrared Thermography (Irt)mentioning
confidence: 86%
“…However, Rocha et al [106] validated this method as an indicator of stress by assessing variations in surface temperature at one of two anatomical locations -the back or rump [105,107,108] -or at multiple anatomical sites [40,103]. To this end, Rocha et al [106] measured the temperature responses of 120 pigs on the neck, rump, orbital region and area behind the ears under two conditions: gentle handling-induced stress without exposure to stressors versus rough handling that included abrupt movements, loud noises and/ or physical contact with the personnel. In addition, they evaluated short (30 min) vs. long (90 min) distances walked by pigs and the time travelled (40 min at a loading density of 0.46 m 2 /pig) in a single-deck trailer.…”
Section: Infrared Thermography (Irt)mentioning
confidence: 98%
See 2 more Smart Citations